2021
DOI: 10.1007/s11897-021-00528-9
|View full text |Cite
|
Sign up to set email alerts
|

Optimal CRT Implantation—Where and How To Place the Left-Ventricular Lead?

Abstract: Purpose of Review Cardiac resynchronization therapy (CRT) represents a well-established and effective non-pharmaceutical heart failure (HF) treatment in selected patients. Still, a significant number of patients remain CRT non-responders. An optimal placement of the left ventricular (LV) lead appears crucial for the intended hemodynamic and hence clinical improvement. A well-localized target area and tools that help to achieve successful lead implantation seem to be of utmost importance to reach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 75 publications
1
21
0
Order By: Relevance
“…For years, the statement that nearly onethird of CRT patients do not respond to resynchronization therapy has become general knowledge. It is discussed and partially accepted without questioning the reasons [2]. Besides optimal programming of the CRT device, the anatomical structure of the coronary system plays the most crucial role.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For years, the statement that nearly onethird of CRT patients do not respond to resynchronization therapy has become general knowledge. It is discussed and partially accepted without questioning the reasons [2]. Besides optimal programming of the CRT device, the anatomical structure of the coronary system plays the most crucial role.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the attainable vessels were counted for possible LV lead placement. For accessible vessels for the CRT, the size of 5.1 F (1.7 mm) and angle is less than 60° [2] are considered. The size over 1.7 mm was found in 23/26 PVLV and 10/15 LMV in nonischemic-HF and 28/29 and 16/21 in ischemic-HF.…”
Section: Quantitative Datamentioning
confidence: 99%
“…Positioning of the LV electrode has long been a main concern for response and is still reported to be associated with outcome ( Kutyifa et al, 2018 ). Further it is suggested that having an overview of the myocardial substrate in terms of fibrosis and scarring ( Butter et al, 2021 ), as well as myocardial activation and coronary venous anatomy before the procedure would be beneficial. This makes it possible to plan the procedure and to aim for placing the LV lead in a coronary sinus branch over a viable myocardial region with late electrical activation.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the considerations to be aware of in this process are the following: is it possible to use a quadripolar lead to be placed into a stable position, not prone to dislodgement, and is the lead in an anatomically favorable position to pace the nonapical posterolateral part of the left ventricle? [16,17] To ensure these issues, it is selfevident that a complete overview of the CS anatomy and ability to reach all the possible targets with the delivery tools are imperative.If the implantation technique does not include these options, the operator is often forced to choose a lead to negotiate the given anatomy of the proximal part of the target vein, e.g. use a LV lead with a very wide curve or with an active fixation mechanism in a large diameter and/or noncurved vein, as it is not possible to be certain that the tip of a smaller curved passive fixation lead is fully wedged into a small side branch and thus securely placed (see figure 6).…”
Section: Choosing the Right And Stable Position For The Leadmentioning
confidence: 99%